Upaya Meningkatkan Prestasi Belajar Siswa Kelas VI SD Negeri 024 Melalui Media Sharing Audio Visual Pada Materi Iman Kepada Hari Akhir Tahun Pelajaran 2017/2018 - Neldawati Neldawati (STKIP Rokania Pasir Pangaraian, 2018)
This study aims to improve the learning outcomes of Religion about the material of faith in the final day by using Audio Visual in grade 6 students of SD Negeri 024 Rambah,, kec Rambah Rokan Hulu District. The subject of this research is the students of class VI SD Negeri 024 Rambah which amounted to 22 students. Action research is carried out in 2 cycles. Data collection in this study using test and observation methods. The result data of the research on the addition and reduction material were analyzed by quantitative descriptive. The results showed that learning by using Audio Visual media can improve the learning result of Religion on the Faith on the final day in class VI SD Negeri 024 Rambah, which in the initial condition of the results before the action was given an average score of 71.42. In the first cycle by using Audio Visual media an increase so that the average value of the class to 28.6. In the second cycle showed an increase with an average of 85.71